Logical thinking and computational programmatics in engineering students - More Valencia, Rubén Alexandre; Tume Ruiz, Juan Manuel; Rangel Vega, Antia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The purposes of studies on computational logical thinking foresee that it is possible, through experiment work, to do research on previous skills of logic and mathematics in engineering students, by using packages of software and applications and supporting these students in parallel. It was possible that teachers achieved impact by using co-creation, and, since their work was collaborative, this showed leadership, motivation, and guidance. By using computer programming and analytical tools integrated into the capacities of students, this not only allowed collaboration, but also development and progress for building their own knowledge, in a process according to the pedagogical theory of constructionism.